(untitled) (Journal of Engineering, 2011)
The major objectives of this research are to analyze the behavior of road embankments reinforced with geotextiles constructed on soft soil and describe the finite element analysis by using ANSYS program ver. (5.4). The ANSYS finite element program helps in analyzing the stability of geo- structure (embankment) in varied application of geotextiles reinforcement to enhance the best design for embankment. The results of analysis indicate that one of the primary function of geotextiles reinforcement was to reduce the horizontal displacement significantly. With the inclusions of reinforcement, the horizontal displacement reduced by about (81%), while the vertical displacement reduced by (32%). The effect of geotextiles stiffness modulus on horizontal and displacement is quite significant even a very high modulus of geotextile will have relatively little effect on vertical displacement. Also it is observed from the obtained results that the maximum displacement occurred at the toe of embankment for both horizontal and vertical movement, then decrease gradually to a negligible value for the layer reinforced case. Also the reinforcement reduces the shear stress developed in the foundation soil.